9 - The Green Paper on the State of the Nigerian Economy - Journal System (Africa Development, 1984)
* Views of the Workshop on the State of the Nigerian Economy, the Report of the National Economic Council's «Committee of Experts» and the Federal Government White Paper (26th Oct., 1983)